Development of Instructional Package for Marine Automation Course (IPMAC) of the Marine Engineering Department of the Philippine Merchant Marine Academy - Wenceslao M. Cawagas III (Future Science / FSH-PH Publications, 2026)
Maritime systems are becoming increasingly automated, creating a need for highly skilled engineers in marine automation with strong knowledge of control engineering, instrumentation, and ways to run automated systems. The inadequacy of traditional teaching techniques to offer sufficient interactivity, accessibility, and uniformity needed for learning in a technologically complex world has resulted in a need for new forms of delivering instruction. This study aimed to produce, implement, evaluate a web-based instructional package that would improve teaching of Basic Control Engineering (BCE) through use of an Internet-based package (IPMAC) at the Philippine Merchant Marine Academy. The IPMAC system was developed using PHP and MySQL, and had interactive lecture presentations, visualisations of control systems, automated assessment and feedback, and an ability to monitor progress, all from one web-based application. A descriptive evaluative research methodology was developed to assess the usability, effectiveness and satisfaction of use by Engineering students at the Philippine Merchant Marine Academy, faculty members, and IT professionals through a structured survey. Based on the answers provided by participants, all participants agreed that using this system was useful in providing support for their lesson plans and keeping students engaged throughout the learning process. Participants also indicated they better comprehended the concept of automation and that they could successfully teach students both the benefit of automated systems as well as the effectiveness of using automated systems when teaching students through assessments/tests.